Kajian Etnomatematika pada Makanan Tradisional Minangkabau (Studi Kasus pada Lamang, Kue Basung, Onde-Onde, dan Kue Mangkuak) - Muhammad Fachri Muslim; Arnellis Arnellis; Ahmad Fauzan; Yerizon Yerizon (Jurnal Penelitian Pendidikan IPA, 2025)
This study addresses the limited exploration of mathematical concepts embedded in Minangkabau traditional food practices, despite their potential to support culturally relevant mathematics learning. The research aims to identify and describe the ethnomathematical elements found in the preparation of four traditional foods: lamang, basung cake, onde-onde, and mangkuak cake. A qualitative approach was employed using ethnographic and case study methods. Data were collected through participant observation, in-depth interviews with traditional food makers, visual documentation, and supporting literature. The data were analyzed using thematic analysis combined with mathematical and geometric identification techniques to uncover measurement, proportional reasoning, and geometric structures. The findings reveal that traditional food preparation integrates various mathematical concepts, including ratios, volume and weight measurement, symmetry, cylindrical and conical geometry, and time estimation. These concepts appear in ingredient measurement, shaping techniques, folding patterns, and cooking management, although practitioners apply them intuitively without formal notation. The study concludes that Minangkabau culinary practices represent rich sources of ethnomathematical knowledge that can be integrated into mathematics education. This integration has the potential to enhance meaningful learning, connect mathematics with students’ cultural experiences, and support the preservation of local heritage.